Analysis of spatiotemporal land use change characteristics in the upper watershed area of the Qingshui River basin from 1990 to 2020 - Wang, Lei; Wang, Na; Pang, Min; Zhang, Qing; Wei, Dan; Li, Yan; An, Zhizhuang; Jin, Liang (Frontiers in Environmental Science, 2024)
Land use land cover (LULC) change is an important factor driving global change, influenced by the interaction between human activities and natural ecosystems. The upper watershed of the Qingshui River is adversely affected due to anthropogenic activities. Therefore, analyzing the driving factors of land use changes in this area is crucial for ecological protection and sustainable development.Based on the long-term Landsat image data from 1990-2020, the spatiotemporal change characteristics of the LULC rate and its driving factors in the upper watershed of the Qingshui River basin were analyzed using the land use transfer matrix and dynamic degree of land use processes. The redundancy analysis was performed to investigate the links between LULC changes, socio-economic and climatic variables. Results showed that from 1990-2020, the area under waters and woodland decreased by -2.94 km 2 and -451.44 km 2, respectively. Meanwhile, grassland, arable land, construction land, and unused land area increased by 278.71 km 2 , 115.72 km 2 , 46.48 km 2 and 13.49 km 2 . In terms of the proportion area to the total land (2334.10 km 2 ), woodland accounted for 63.43-44.09% of the total land and was mainly distributed in the east; arable land was 17.00-21.96% and was largely distributed on both sides of the middle and lower parts of the basin; construction land comprised 1.03-3.02% and was generally found in flat areas near the downstream and water area was only 0.1-0.01% which primarily covered the Qingshui River and its tributaries from 1990-2020. Construction and unused lands showed the fastest rate of change, followed by water area and grasslands. Accelerated urbanization, rapid socio-economic development, and the farmland-to-forest policy were the main driving forces behind the change in LULC in the upper reaches of the Qingshui River. The findings of this study can assist in planning strong management strategies for ecological protection and socioeconomic sustainable development in the study area.